Papers - Domestic Production - Petroleum Development in Southwest, Texas during 1929 - O. G. Bell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
While all of the Southwest Texas fields lie within the Gulf Coastal Plain this area may be divided into three subdivisions—the Coastal Plain zone proper, the Reynosa Escarpment zone, and the interior zone. The Coastal zone includes that strip adjacent to the Gulf of Mexico and . extending inland for a distance of about 60 miles and includes the Palo Blanco, Palangana, Piedras Pintas, Kingsville, Agua Dulce, Saxet, White Point and Refugio fields. The Reynosa Escarpment zone includes a Pliocene overlap over older Tertiary sediments lying west of the Coastal zone. The western margin of the Reynosa formation forms a more or less well-defined westward facing escarpment with which the so-called Reynosa Escarpment fields are indirectly related. These fields include those in eastern Zapata, eastern Webb, western Jim Hogg, western Duval, McMullen, Live Oak, Bee, Goliad and Victoria counties. The interior zone includes these fields west of the Reynosa Escarpment which are not in any way related to it and are on separate types of structure. Production data by fields and wells are shown in Table 1. Roma.—During 1928 the Texas Co. completed two small gas wells at 198 ft. on the Roma Structure near the town of Roma on the Rio Grande in Starr County. This gas is of no commercial importance but was used for fuel in drilling other deep tests on this structure. Three dry holes ranging from 3600 to 4200 ft. were drilled; then their No. 4 Guerra, the fourth deep test, was completed during December as a small producer of 37" Bé. oil from a sand at 3560 to 3590 ft. No production was marketed during December but arrangements were being made to handle the output from this well during 1930. This is the first commercial producer in Starr County. Driscoll.—In 1929, Robert Driscoll discovered gas on his Santa Rosalia Ranch in Duval County while drilling water wells. Two sands were developed, one at 2400 ft. and another at 2936 ft. and several gas wells were completed in each, ranging in volume from 15,000,000 to 40,000,000 cu. ft. and in reservoir pressure from 500 to 1,000 Ib. Early in January of 1929, Mr. Driscoll's No. 14 Fee was completed as a 50-bbl. oil producer at 2894 ft. Two other oil producers were completed early in 1929. Mr. Driscoll's death early in the year curtailed develop-